Implementasi Nilai-nilai Multikulturalisme dalam Menanamkan Moderasi Beragama di Pesantren - Mo'tasim Mo'tasim (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
The government is currently promoting a program to strengthen religious moderation through the Ministry of Religion. However, the program is not optimal if it is not supported by all parties, especially from the education sector. Therefore, Islamic boarding schools can become supporting partners in line with the Islamic boarding school culture which prioritizes togetherness in religion. This qualitative research seeks to analyze in depth how the culture of the pesantren is sublimated to multicultural values, which lead to an attitude of religious moderation. The Pesanten Al-Ibrohimy that located in Galis village, Galis sub-district, Bangkalan district is the object of this research. The results of the study show that Islamic boarding schools with their multicultural character educate their students to become moderate religionists, so that they can cope with cultivating inclusive thinking and attitudes. Therefore, the values ​​of multicultural education must continue to be produced in a sustainable manner, as a concrete form of pesantren's contribution to the development of education in Indonesia.